Analysis and Perspective on Heat Pump for Industrial Steam Generation. Issue 5 (8th March 2021) - Yan, Hongzhi; Wang, Ruzhu; Du, Shuai; Hu, Bin; Xu, Zhenyuan
Abstract : Steam generation process is closely related to energy conversion and cleaner energy utilization, and the industrial steam is even regarded as the currency of heat with significant social and economic value. Herein, the possible industrial steam generation paths are analyzed based upon thermodynamics analysis, in which fossil fuel, electric, and heat‐pump heating are considered. The large‐temperature‐lift heat‐pump heating for steam generation is proved to be a most reasonable way with high‐efficiency and wide adaptability. Furthermore, a possible system sketch is proposed, in which the heat pump is used for preheating for low‐temperature evaporation and the generated steam can be thus compressed with a steam compressor to the expected high‐temperature (pressure) steam. The key parameters of the heat pump for steam generation are ascertained and the subsequent optimization space is discussed. The results show that the proposed steam‐generation path has clear performance advantages and potential for industrial steam generation, which could be a sustainable heating system for industry. Abstract : The left side shows the heat pump's basic principle; upgrading low‐temperature to high‐temperature by electricity. The "?" indicates the large temperature lift cycle of more than 100 °C. In the upper right corner, steam is widely used in the industrial utilization. The lower right side is the ambient air‐ a proposed ubiquitous heat source.